Assessment Score Comparison of Knowledge and Clinical Reasoning of Medical Student Educated by Bedside or Conference Room Teaching in Internal Medicine Ward - Sayyd Gholamreza Mortazavimoghaddam (Tabriz University of Medical Sciences, 2017)
Background: Evidence shows that bedside teaching is declining in recent years. One reason is the expectation for students to earn credit. Here, the impact of education method on undergraduate assessment score will be tested. Methods: This is a quasi-experimental study conducted with 66 undergraduate medical students who were allocated into two matched groups on the basis of a pulmonary pathophysiology course score in the internal medicine department of the Birjand University of Medical Sciences (Iran). Chronic obstructive pulmonary disease (COPD) was chosen as the theme of this education. After groups were allocated, training was conducted with 36 students using the Traditional Patient's Bedside Teaching (Tr-BT) method and for 30 students using the Conference Room Case Presentations (Cr-CP) method. Evaluation were conducted at the end of the three-month course period using the Multiple-Choice Questions (MCQ) and Key Feature (KF) examination. Data were analyzed using independent t tests, Mann-Whitney U, and the chi-square test. Results: Among the collected student the scores of KF, inward ratings and MCQ examinations in intern vs extern were (8.58 ± 1.46 vs 8.31 ± 1.58; P = 0.65), (14.75±1.54 vs 15.51±1.88; P = 0.08),( 10.77 ± 2.20 vs 10.47 ± 1.61; P = 0.55) respectively. The mean of the pulmonary pathophysiology score was 13.03 ± 1.66 in the Tr-BT group compared with 12.67 ± 1.92 in the Cr-CP group (P = 0.23). The means of the MCQ scores were 10.07 ± 2.13 and 11.37 ± 1.56 in the Tr-BT and Cr-CP groups, respectively (P = 0.007). Conclusion: The score of the MCQ exam was significantly higher in the group taught using the Cr-CP method. Students and teachers may prefer Cr-CP. To increase interest in bedside teaching, the assessment methods of medical students should be based on practical and clinical judgment evaluation.